2019
DOI: 10.1039/c9ra02496d
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evaluation of the subchronic systemic toxicity of akermanite bioceramic for bone regeneration following ISO standard methods

Abstract: This study demonstrated that the extracts of akermanite bioceramic did not cause in vivo subchronic systemic toxicity and suggested that Ca2MgSi2O7 with desirable biocompatibility may be a potential candidate for orthopedic clinical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…They must possess some characteristics, such as appropriate micro-architecture (e.g., porosity and pore size) and surface chemistry, to support cell metabolism, cell adhesion in vitro, growth, and phenotype preservation, thereby providing the necessary space for neovascularization in vivo. [1][2][3] At present, numerous materials have been used for the preparation of scaffolds for bone tissue regeneration; three main types of materials have been classied, including polymers, 4,5 bioceramics, [6][7][8] and composites. [9][10][11][12] Natural bone exhibits a hierarchical structure consisting of collagen brils, and hydroxyapatite nanocrystallites (nHAp), which are the organic and inorganic components, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…They must possess some characteristics, such as appropriate micro-architecture (e.g., porosity and pore size) and surface chemistry, to support cell metabolism, cell adhesion in vitro, growth, and phenotype preservation, thereby providing the necessary space for neovascularization in vivo. [1][2][3] At present, numerous materials have been used for the preparation of scaffolds for bone tissue regeneration; three main types of materials have been classied, including polymers, 4,5 bioceramics, [6][7][8] and composites. [9][10][11][12] Natural bone exhibits a hierarchical structure consisting of collagen brils, and hydroxyapatite nanocrystallites (nHAp), which are the organic and inorganic components, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Τhe systemic toxicity of akermanite bioceramics was already investigated following well-accepted ISO standard methods in healthy adult rats. The injection of akermanite extracts in Wistar rats did not cause pathological changes to important organs, thus indicating the biosafety of akermanite bioceramics in clinical applications [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in vivo implantation of two types of scaffolds resulted in acute toxicity and the disturbance of phosphorus homeostasis. This is due to the binding of phosphorus from the blood serum, thus creating hypophosphatemia and hemolysis [ 60 ]. To address the dose-dependent toxicity of akermanite, however, more research is required [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of a porous preform, before sintering, the complete densification of struts is not always desirable 1 . Components with a complex pore distribution are becoming increasingly attractive for improved cell attachment, growth, and differentiation, as well as vascularization 13,14 …”
Section: Introductionmentioning
confidence: 99%
“…1 Components with a complex pore distribution are becoming increasingly attractive for improved cell attachment, growth, and differentiation, as well as vascularization. 13,14 The present paper is aimed at providing fundamentals of the sintering and crystallization of åkermanite glass-ceramics with stoichiometric composition, starting from glass microspheres produced by flame synthesis. The results of a preliminary additive manufacturing (AM) study are also shown.…”
mentioning
confidence: 99%